ANALISIS NILAI TAMBAH KOPI LONG BERRY DI KABUPATEN ACEH TENGAH (Studi Kasus Home Industry Kawa Gayo) - Nasution, Wahyu Isnanda; Puarada, Sakral Hasby; Yanto, Nopri; Zuliati, Septiarini; Hidayatsyah, Hidayatsyah (Universitas Quality, 2024)
This research aims to compare the value-added in the production of green bean long berry coffee variants in Kawa Gayo home industry in Central Aceh Regency with the production of long berry coffee powder variants that are ready to be brewed and consumed. This value-added analysis research uses the Hayami method. Sample determination in this research uses purposive sampling method where the researcher relies on their own judgment when selecting population members to participate in this research. The data used in this research include primary data and secondary data. The results of the research show that the value-added of the green bean long berry coffee variant is greater than that of the long berry coffee powder variant, with a value-added amounting to Rp. 8,500. This is in line with the total profit obtained by Kawa Gayo home industry through the production of green bean long berry variant, which is greater with a total profit of Rp. 116,000 compared to the production result of long berry coffee powder variant. Besides the scale of the business, the factors influencing the greater value-added of the green bean long berry variant are influenced by the low contribution of other inputs, as Kawa Gayo home industry uses very few third parties in its production activities.